2019
DOI: 10.1002/maco.201911053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated brazing on the microstructure and corrosion behavior of twin roll cast AA3003

Abstract: Aluminium alloy (AA) 3003 is widely used as fin and tube material in heat exchangers. In these heat exchangers the tube and fin material are brazed together by means of an AA4xxx alloy. In this work, the effect of a simulated brazing step on the microstructure and corrosion behaviour of a twin roll casted (TRC) AA3003 was studied. In particular, the effect of simulated brazing on the corrosion properties of the centre line segregation (CLS) of alloying elements and the interaction of the intermetallic particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, some published studies can be found in which topography maps acquired simultaneously or associated with relevant potential maps are neglected and not shown when presenting SKPFM results. 2,4,6,51,[61][62][63][64] Even though the most pertinent information concerning corrosion studies is contained in the CPD maps, this practice is highly discouraged. Topography images are relevant to visualize correlations between topographical features and Volta potential differences accurately.…”
Section: Volta Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some published studies can be found in which topography maps acquired simultaneously or associated with relevant potential maps are neglected and not shown when presenting SKPFM results. 2,4,6,51,[61][62][63][64] Even though the most pertinent information concerning corrosion studies is contained in the CPD maps, this practice is highly discouraged. Topography images are relevant to visualize correlations between topographical features and Volta potential differences accurately.…”
Section: Volta Potentialmentioning
confidence: 99%
“…Several examples of histogram analysis of Volta potential data can be found in previous studies. 28,56,61,62,[69][70][71][72][73][74][75] The use of histograms not only allows the calculation of the most representative potential values characterizing the different phases mapped (and their Volta potential differences), but also provides a measure of their individual potential distributions through their standard deviations (calculated from the FWHM -full width at half maximum-of the multinomial peak simulation of the histogram). 62,[73][74][75] An example of a multinomial peak de-convolution analysis of the histogram acquired from a CPD image is shown in Fig.…”
Section: Volta Potentialmentioning
confidence: 99%